Gravidez em jovens que convivem com HIV por transmissão vertical - desfechos, desafios e implicações para o cuidado - Santos, Denise Lopes [UNIFESP] (2019)
Introduction: The first cases of pregnancy in women infected with HIV by vertical transmission were described in 1998 and since this first notification, few publications have been made in order to better understand this aspect of the HIV infection epidemic. Most young women infected by vertical transmission are followed up in pediatric clinics and adolescents until adulthood, but data on their reproductive health are poorly described in Brazil. The purpose of this study was to evaluate a retrospective cohort of girls who acquired the infection perinatally, reached reproductive age and are mothers. This group was compared with HIV-infected pregnant women through a transmission route other than perinatal. The clinical outcome of pregnancy and childbirth, in addition to the evaluation of pregnancy products for 12 months, were compared between the two groups. Objectives: To characterize the population of pregnant women infected with HIV by vertical transmission and their concepts, in a cohort of adolescent children and young people attended at a reference service in São Paulo and to compare this group of pregnant women with a group of pregnant women infected with HIV by other means except perinatal and its concepts. Method: this is a retrospective observational epidemiological study carried out at the Pediatric Infectious Diseases Service Center (Ceadipe) of Hospital São Paulo / Escola Paulista de Medicina / UNIFESP, carried out from July 2017 to July 2019. Results: The young women in the TV group compared to the TH group were younger at the time of delivery (mean - 20.6 years X 31.1 years - p * <0.001), single (56.7% X 29.5% - p * = 0.007), primiparous (71.9% X 22.9% - p * = <0.001) and belonged to the white race (84.1% X 67.8% - p * = 0.037). In addition, schooling was higher in the TH group (p * = 0.03). The use of cTARV before pregnancy (96.9% X 72.9% - p * <0.03), was higher among pregnant women in the TV group when compared to those in the TH group. During the first trimester of pregnancy, however, this difference was not statistically significant (71.9% X 65.6% - p * = 0.514). Despite being the group that most used cTARV before pregnancy, the TV group was the one that at the beginning of pregnancy had higher HIV viral loads, with HIV viral load> 1000 copies and few pregnant women below the level of detection when compared with the TH group, respectively (66.7% X 41.0% and 10% X 47.5% -p * = 0.01). The pregnant women in the TV group also had a higher proportion of CD4 + T cell count <500 cells / mm3 (76.7% X 51.1% - p * <0.001), but with an evident response in the peripartum, with HIV CV below similar detection level (63.3% X 81.3% - p = 0.089) and CD4 + T cell count above 200 / mm3, in a lower proportion than those in the TH group (62.5% X 95.5% - p * = 0.001). In the TH group, 18.5% of the pregnant women were obese and 40% were overweight, and in the TV group there were 8% of obese pregnant women and 20% were overweight, the difference being statistically significant (p * = 0.031). in good condition, with a similar average birth weight in both groups (2922g X 2930 g –p = 0.940), with an average Z-score between -2 and +2 for weight 84.4% X 85.6% - p = 0.677), between -2 and +1 for BMI (81.2% X 77.8% - p = 0.741) and weight / height (74% X 67.9% - p = 0.826). We had premature delivery in two of 32 pregnancies in the TV group and twelve of 97 pregnancies in the TH group (6.2% X12.3% p = 0.515). The infants of the two groups evolved with good weight-height gain, but we observed an increase in BMI and P / E rates with a Z-score greater than 1, for BMI and P / E, indicating a risk for overweight and overweight, the difference between groups was not statistically significant, but it is clinically relevant. We found loss of vaccination opportunity in infants for all vaccines, with a statistically significant difference between the TV and TH groups for the hepatitis B vaccines (37.5% X 5.1% - p * <0.001) and Rotavirus (25 , 8% X 6.4% - p * = 0.003). We did not have HIV transmission in both groups. Conclusion: Pregnant women in the TV group, even with early diagnosis, and access to treatment for a longer time, have greater difficulty in controlling HIV replication and maintaining the CD4 + T cell count. During the evolution of pregnancy these pregnant women showed control of HIV viral load and improved CD4 + T cell count. The newborns were born in good condition and evolved with adequate weight-height gain; in some, risk for overweight and overweight was observed. There were no cases of vertical transmission of HIV. There are missed vaccination opportunities in infants in both groups, most evident in the hepatitis B and rotavirus vaccines.